2021
DOI: 10.3389/fonc.2020.625459
|View full text |Cite
|
Sign up to set email alerts
|

Which Definition of Upper Rectal Cancer Is Optimal in Selecting Stage II or III Rectal Cancer Patients to Avoid Postoperative Adjuvant Radiation?

Abstract: BackgroundIn most guidelines, upper rectal cancers (URC) are not recommended to take neoadjuvant or adjuvant radiation. However, the definitions of URC vary greatly. Five definitions had been commonly used to define URC: 1) >10 cm from the anal verge by MRI; 2) >12 cm from the anal verge by MRI; 3) >10 cm from the anal verge by colonoscopy; 4) >12 cm from the anal verge by colonoscopy; 5) above the anterior peritoneal reflection (APR). We hypothesized that the fifth definition is op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A 2021 single-center retrospective study from China evaluated 222 patients with stage II and III rectal cancer located entirely above the peritoneal reflection and also reported that postoperative radiation therapy had no impact on LR. 27…”
Section: Certainty Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A 2021 single-center retrospective study from China evaluated 222 patients with stage II and III rectal cancer located entirely above the peritoneal reflection and also reported that postoperative radiation therapy had no impact on LR. 27…”
Section: Certainty Of Evidencementioning
confidence: 99%
“…A 2021 single-center retrospective study from China evaluated 222 patients with stage II and III rectal cancer located entirely above the peritoneal reflection and also reported that postoperative radiation therapy had no impact on LR. 27 The recently published PROSPECT trial did not exclusively study patients with upper rectal cancer but presented an alternative treatment paradigm that deserves more study and could be potentially extrapolated to this population of patients. The study was a multicenter, noninferiority randomized trial of 1194 patients.…”
Section: Tumors Of the Upper Rectum Do Not Usually Benefit From Neoad...mentioning
confidence: 99%